Saveet Ventures Inventory Management Web-based System - Selvaraj, Katyaayani; Azizul Azhar Ramli (Applied Information Technology And Computer Science, 2025)
With the growing technology in business operations, the need for effective inventory management systems has become increasingly critical. Saveet Ventures, a veterinary product supplier in Negeri Sembilan, currently relies on manual methods like spreadsheets and physical records. This approach creates challenges like limited real-time visibility, frequent stock discrepancies, and inefficient data management. This project aims to design, develop, and test web-based inventory management system using a structured approach and prototype model tailored to address these challenges by using Visual Studio Code and DBeaver. The proposed system replaces existing manual processes with an automated platform that integrates essential modules, including login and registration, vendor management, inventory management, customer management, sales, and report generation. The development follows the prototype model, incorporating user feedback through iterative testing. The findings highlight the system’s strength in delivering real-time inventory tracking through low stock notifications, minimizing human error, and enhancing decision-making with reporting and data visualizations.